IMPLEMENTASI KURIKULUM MERDEKA DALAM PROSES PEMBELAJARAN BAHASA BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI TINGKAT SMA DI KOTA PADANG - Khairatunnisa Nisa (Jurnal Pendidikan (Teori dan Praktik), 2022)
This study was motivated by the introduction of an autonomous curriculum into Indonesia's educational system. The purpose of this project is to demonstrate the use of an independent curriculum and information and communication technologies in the high school level language acquisition process in Padang. This applies to qualitative field research. Inductive analysis was utilized to analyze the data after it had been collected via triangulation, and the research results revealed more than generalizations. This research is descriptive qualitative because it is in the form of existing facts and aims to show a problem and scenario as they are, which is investigated and as a whole. The results of this study demonstrate that autonomous curricula contain the notion of employing a curriculum that is in line with students' requirements and that, in the context of learning recovery, must pay attention to student competency attainment in educational units. The goal must be achieved via utilizing ICT in learning, particularly language acquisition. E-books, email, mobile devices, digital cameras, MP4 players, websites, wikipedia, YouTube, web-blogs, and podcasting are just a few examples of the many information and communication technologies that can be used for language acquisition.